“Physically We Are Apart, Mentally We Are Not.” Creating a Shared Space and a Sense of Belonging in Long-Distance Relationships - Kolozsvari, Orsolya (Qualitative Sociology Review, 2015)
As couples tend to be referred to as “being together,” long-distance partners, who spend most of their time apart and in diff erent spaces, might face a challenge delineating and validating their relationship. Through in-depth interviews with 20 couples in a long-distance relationship, this study explores how long-distance partners linguistically and symbolically mark the boundaries of their relationship, and also transcend any real or perceived gaps between distance and closeness in the process. While they rarely shared a physical space, my participants created joint socio-mental spaces, which enhanced their sense of belonging and helped to expand defi nitions of intimacy and space.